Data privacy preservation for the search of Internet of things based on fine-grained authorization - Jia-hui WANG; Chuan-yi LIU; Bin-xing FANG (网络与信息安全学报)
With the rapid development of the Internet of things (IoT) technology and cloud computing technology, the search engine for Internet of things become a hot research topic. However, because of the openness of the search of IoT, the privacy in traditional Internet search area becomes more prominent and faces more challenges. Firstly, the research background and challenges of data privacy preservation for search of IoT were described. Secondly, the scheme of data privacy preservation for the search of Internet of things based on fine-grained authorization was pro-posed, which combined the encrypted search algorithm with the attribute based access control algorithm. Thirdly, the security analysis and performance analysis of the scheme were also carried out. Finally, the future research work was summarized and pointed out.